All-optical 2r regenerator based on self-phase modulation - Mat Yaacob, Siti Nurul Sharina (2020)
Nowadays, optical regeneration is getting popularity as it provides an effective way of coping with transmission impairment. Transmission impairments degrade the quality of optical signals and thus, ultimately limiting the achievable transmission distance. Optical 2R regenerators provide an effective way of coping with transmission impairments by restoring the quality of optical signals through re-amplification and reshaping (2Rs), thereby enabling reliable transmission over long distances. In this work, All-Optical 2R Regeneration which is based on self-phase modulation (SPM) in a single highly nonlinear fiber (HNLF) with 2500 km length of transmission is investigated. In addition, there are two types of modulation format namely, non-returnto-zero on-off keying (NRZ-OOK) and return-to-zero on-off keying (RZ-OOK) were investigated. Both of these modulation techniques were performed in two stages which are the degradation and regeneration stages. The simulation results show that the NRZOOK and RZ-OOK have significant improvement after the regeneration stage. For NRZ-OOK, the maximum Q-factor before and after the regeneration stage are 3.751 and 5.859, respectively. The minimum bit error rate (BER) after the degradation stage is 10-5 and is further improved to 10-9 after the regeneration stage. For RZ-OOK, the maximum Q-factor before and after the regeneration stage are 4.514 and 6.768, respectively. The minimum bit error rate (BER) after the degradation stage is 10-6 and is further improved to 10-12 after the regeneration stage.